Short Communication: Plants used by Sundanese mothers for maternal care in a rural village in Bandung District, West Java, Indonesia - DINA OKTAVIA; QORINAH ESTININGTYAS SAKILAH ADNANI; LANI GUMILANG; EVI NOVIANTI; SUNARDI SUNARDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oktavia D, Adnani QES, Gumilang L, Novianti E, Sunardi. 2023. Short Communication: Plants used by Sundanese mothers for maternal care in a rural village in Bandung District, West Java, Indonesia. Biodiversitas 24: 3568-3573. Traditional beliefs and plants are pivotal during pregnancy, childbirth, and postpartum. Little is known of Sundanese, a small ethnic group whose traditions and use of plants facilitate easier pregnancy, birth, and postpartum recovery. This study aimed to determine the traditional beliefs and types of plants used by Sundanese mothers of Bandung District, West Java, Indonesia during pregnancy, childbirth, and postpartum care. Individual interviews using structured questions were conducted to collect socio-demography data and gather information on traditional beliefs and the use of plants concerning pregnancy, childbirth, and postpartum care. Purposive and snowball sampling was employed to enroll women of reproductive age who were either pregnant at the time of the study or had recently given birth and were postpartum. Data were collected from 119 Sundanese women. These women frequently used 25 different medicinal plant species from 21 families to treat various conditions that arise during pregnancy and childbirth. The Zingiberaceae plant family was observed to be the most commonly used, with leaves being the most frequently utilized plant part. Decoction and cooking were reported as the most favored remedy preparation. The most effective plants during pregnancy, childbirth, and postpartum were Cocos nucifera L., Cocos nucifera L., and Sauropus androgynus (L.) Merr., respectively. Therefore, to promote sustainable women's health in rural areas, the current findings highlight the necessity for conservation efforts and further studies on the phytochemical and pharmacological aspects of frequently used food and medicinal plants.